2020
DOI: 10.1016/j.snb.2019.127213
|View full text |Cite
|
Sign up to set email alerts
|

Low cost fabrication of microfluidic paper-based analytical devices with water-based polyurethane acrylate and their application for bacterial detection

Abstract: This study presents a simple, inexpensive and environment-friendly fabrication strategy for microfluidic paperbased analytical devices which can resist the penetration of surfactant solutions and organic solvents, by using water-based polyurethane acrylate via UV light curing. The filter paper's barrier created using cured PUA could withstand surfactant solutions (10 wt%, CTAB, SDS and Triton X-100) and organic solvents (methanol, isopropanol, DMF, DMSO, etc). This is very useful for analyzing complicated biol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(40 citation statements)
references
References 49 publications
(52 reference statements)
0
40
0
Order By: Relevance
“…The bacteria in water samples are pre-concentrated using antibody-coated immune-magnetic nanoparticles and then tested with the paper-based microfluidic device. Similarly, Lin et al [ 22 ] recently showed in their study that a PUA cured paper-based device can potentially detect microbes present in some aggressive liquids. Molina et al [ 23 ] used a different strategy for differential identification of bacteria with the aid of multiplex PCR.…”
Section: Introductionmentioning
confidence: 92%
“…The bacteria in water samples are pre-concentrated using antibody-coated immune-magnetic nanoparticles and then tested with the paper-based microfluidic device. Similarly, Lin et al [ 22 ] recently showed in their study that a PUA cured paper-based device can potentially detect microbes present in some aggressive liquids. Molina et al [ 23 ] used a different strategy for differential identification of bacteria with the aid of multiplex PCR.…”
Section: Introductionmentioning
confidence: 92%
“…[18][19][20] PDMS is the most common material used to fabricate microuidic devices because of the ease of fabrication, optical transparency, gas permeability, low chemical reactivity, and inexpensiveness. 17,21,22 It is also used in bioassays and targeted drug delivery systems (DDS) using implantable microuidic devices. 23 The microstructure is generally fabricated by so lithography.…”
Section: Microfluidicsmentioning
confidence: 99%
“…1,[29][30][31][32][33] These mPADs were used to perform analytical assays for point-of-care diagnostics and environmental monitoring. 2,18,19,28,[34][35][36] Such methods of fabrication required particular materials (synthetic hydrophobic precursor [37][38][39] and photoresist 1,32 ) and equipment (wax printer, 20,21,[40][41][42][43][44][45] inkjet printer, 22,23 laser, 39,45 mask aligner, 1 and UV lamp 32,33,37,38 ) to create the devices. Fabrication of mPAD has been initially demonstrated via photolithography, while direct printing of hydrophobic materials has been developed as alternative routes.…”
Section: Introductionmentioning
confidence: 99%